Introduction: Social classes and cultural consumption - –a highly contested relationship - Εμμανουήλ, Δημήτρης; Καυταντζόγλου, Ρωξάνη; Σουλιώτης, Νίκος (The Greek Review of Social Research, 2016)
The articles in this special issue present the main findings and theoretical conclusions of an empirical research conducted in Athens in 2013 on the relationship between social stratification and cultural consumption in the fields of music, cinema, theater and dance. The introduction outlines the context of the approaches, arguments and basic theoretical concepts and hypotheses that directed the research. The first part considers the different approaches to social stratification and stresses the importance of the neo-weberian distinction between economic class and social status. The second part reviews the main sociological theories on the broad social divisions of cultural consumption since Bourdieu's Distinction. The third part, which completes the introduction, presents the main methodological issues that empirical research in this field confronts, especially decisions concerning the range of cultural activities recorded and the relative importance of practices, preferences and modes of perception and apprehension of cultural goods in the analysis of cultural consumption.